THE ROLE OF 3D ILLUSTRATIONS IN THE DESIGN OF A CHILDREN’S BOOK - Головачук , І. П.; Воробчук, М. С.; Лелик, Я. Р.; Шмельов, В. М. (Art and Design, 2024)
The aim of the research is a theoretical study of the role of 3D illustration in book design; identifying and displaying the main stages of creating images with three-dimensional objects for a children’s book; clarifying the perspectives of 3D illustrations in creating visual contents of textbooks. Methodology. Analytical and structural approaches, as well as a visual-analytical method of artistic and compositional analysis were used in the development of a three-dimensional illustration for a children’s book. Results. The methods of creating computer illustrations in books are considered and it is established that they can be photorealistic, abstract, vector, contain animation or interactive elements. It is determined that computer animations are easily adapted according to the needs of the developer, so they are convenient and effective to use, and the use of three-dimensional graphics in books is a way to attract the attention of the reader. The main methods of creating three-dimensional illustrations for books are studied and described: the method of anaglyph, thermorelief, tabs with three-dimensional images. The algorithm for creating images with three-dimensional objects for a children’s book using the Cinema 4D program is considered and practically demonstrated. Scientific novelty. The possibilities of using 3D illustrations in the design of books were considered and the features of their application in practice were revealed. A scheme for creating illustrations using three-dimensional objects has been developed. It was determined that three-dimensional images attract the reader with their realism and increase interest in the book. Therefore, creating 3D images using computer technologies is one of the promising areas of art development. Practical significance. The results of the research can be used for further study of the use of 3D illustrations in the design of books, as well as serve as theoretical and practical material for the training of design specialists.